IMPROVING STUDENT’S READING COMPREHENSION THROUGH LOOK AND SAY METHOD - Ernila Junipisa, Ni Made (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2024)
ABSTRACT This research is aimed to find out whether or not the implementation of Look and Say Method improves students' reading comprehension. Look and Say is reading method applied during students’ learning activities. A class of accounting class in Triatma Mulya University is participated as the participant of the study. The required data were collected through the use of questionnaire, observation checklist, and reading test. The data from the questionnaire indicated that students had positive attitude toward the implementation of Look and Say method. They feel that Look and Say method improves their motivation in learning English and brings more fun to the process of learning. Moreover, it was found from observation data that the students were actively participated during Look and Say implementation and they were motivated when comprehending a text by means Look and Say method. Finally, the study proved that Look and Say method improved students’ reading comprehension. Students’ mean score of reading test in the beginning of the study was 50.02 meanwhile, after applying Look and Say Method as reading strategy, their mean scores improved to 72.3 ,77.96 and 86.22